Where's my mom? Resilient maternal preference in post-weaning male and female mice within a multi-chamber social behavior task - Maggie M. Slamin; Indra R. Bishnoi; Izabella M. Bankowski; Haley A. Norris; Evan A. Bordt (Brain, Behavior, & Immunity - Health)
One of the earliest and most important social bonds for many mammals is the bond formed with their mother. Mothers often provide essential benefits for offspring development and survival. Growing evidence suggests that this social bond is retained even when animals gain independence, such as during the juvenile period immediately following weaning. Here, we investigated whether or not juvenile mice (postnatal day [P]26) retain the ability to recognize and prefer their mothers post-weaning. We further investigated the strength of this bond using an acute immune activator. On P26, male and female C57BL/6J mice were intraperitoneally injected with the endotoxin lipopolysaccharide (LPS) or saline control (0.5 mg/kg). Four hours later, mice were subject to a five-chamber social preference task (the AGORA) containing their biological mother, a sex- and age-matched novel mouse, a sex- and age-matched sibling, a novel object, and an empty chamber. Our findings reveal that juvenile mice exhibit a strong maternal preference, which was significantly greater than chance and higher compared to any other social or non-social stimuli. While LPS exposure reduced the time spent investigating all stimuli, juvenile maternal preference was not significantly altered by LPS exposure. These effects were especially pronounced in females, while subtle shifts towards novel exploration began to emerge in males by P26. The novel multi-chamber task employed in the present study offered a more nuanced understanding of how social bonds evolve and vary across sex. The current findings suggest that juvenile mice have a robust social preference for their mother that is resilient to early-life immune activation.